Effect of sofosbuvir and ribavirin treatment on peripheral and hepatic lipid metabolism in chronic hepatitis C virus, genotype 1–infected patients. Issue 3 (28th January 2015) - Meissner, Eric G.; Lee, Yu‐Jin; Osinusi, Anu; Sims, Zayani; Qin, Jing; Sturdevant, Dan; McHutchison, John; Subramanian, Mani; Sampson, Maureen; Naggie, Susanna; Patel, Keyur; Remaley, Alan T.; et al.
Abstract : Hepatitis C virus (HCV) modulates intrahepatic cholesterol biosynthetic pathways to promote viral replication. Chronic HCV infection is associated with altered metabolism, including dyslipidemia and insulin resistance (IR), which contributes to disease progression and influences response to therapy. To further understand the impact of HCV infection on host metabolism, we examined changes in serum lipid profiles and intrahepatic expression of lipid‐related genes during interferon (IFN)‐free treatment of chronic HCV, genotype 1 infection with sofosbuvir and ribavirin (RBV), and explored associations with treatment outcome. Serum lipids (total cholesterol, low‐density lipoprotein [LDL], high‐density lipoprotein [HDL], and triglycerides [TGs]) and hemoglobin A1C (HbA1C) were measured during treatment, while gene expression of lipid‐related genes was assessed using paired pre‐ and end‐of‐treatment (EOT) liver biopsies from 8 patients (n = 7 sustained virologic response [SVR]; n = 1 relapse) and unpaired EOT liver biopsies from 25 patients (n = 17 SVR; n = 8 relapse). Serum LDL concentration and particle size increased early in therapy, whereas TG concentration and very‐low‐density lipoprotein particle size decreased concomitantly, irrespective of treatment outcome. Whereas LDL increased in patients regardless of treatment outcome, average LDL concentration was lower at baseline and post‐treatment in patients who relapsed. Analysis of paired liver biopsies revealed altered expression of genes associated with lipid transport, assembly, and signaling. In unpaired EOT liver biopsies, intrahepatic expression of fatty acid metabolism and lipid transport genes was lower in patients who experienced treatment relapse. Conclusion : Clearance of HCV using an IFN‐free antiviral regimen results in rapid changes in peripheral and intrahepatic metabolic pathways, implicating a direct effect of HCV replication on lipid homeostasis. (Hepatology 2015;61:790–801)